Optimization of Architectural Electroacoustics Design for the Interior Mezzanines of Vertical Buildings - FX Teddy Badai Samodra (International Journal of Technology, 2018)
A science that deals with the transformation of electrical energy into acoustic energy or vice versa, electroacoustic, generates the increased intensity and loudness of sound by mechanical and/or electrical means. Because of the same context, it should be designed simultaneously with the consideration of room acoustics. A vertical building is usually designed separately with architectural aspect and other technical consideration. Interior mezzanine has unique characteristic on propagating sound because its balconies could be an element of room acoustic reflector and absorber, a shelter from noise and a barrier of sound propagation. For optimum music and speech activities, hybrid design strategy of active strategy using electroacoustic combined with the passive method is conducted. This research optimizes room acoustics criteria of variated building models as integrated building system with the loudspeaker. Ecotect Analysis and additional audio programming determine all process by simulating all potential variables. The result shows that 5 m will be the recommended minimum distance of column-loudspeaker placement for mezzanine floor. With the same loudspeaker specification power and frequency, the vertical structure as the armature of electroacoustic orientation and interior material are the most critical variables in determining of reverberation time optimization.